2015
DOI: 10.1038/srep08087
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-148b suppresses cell proliferation and invasion in hepatocellular carcinoma by targeting WNT1/β-catenin pathway

Abstract: Accumulating evidences indicate that microRNAs play a vital role in regulating tumor progression. However, the roles of miR-148b in hepatocellular carcinoma (HCC) are still largely unknown. In this study, our data showed that miR-148b was significantly downregulated in 40 pairs of human HCC tissues. Further, the deregulated miR-148b was significantly correlated with larger tumor size, more tumor number, metastasis and worse prognosis in HCC. Overexpression of miR-148b inhibited HCC HepG2 cells proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 47 publications
2
72
1
4
Order By: Relevance
“…Nonetheless, they had neoplastic cells with nuclear Cyclin D1 signal, which suggests that DEN-induced hepatocellular tumors of mice at the stage of adenoma do not require nuclear β-catenin for the initial stages of Cyclin D1 upregulation. On the other hand, however, the disruption of the Wnt/β-catenin pathway in the present study worked to suppress Cyclin D1 in the mouse tumors, which is similar to what has been frequently reported in studies using mouse models of HCC (4,13,20,22,36,46).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Nonetheless, they had neoplastic cells with nuclear Cyclin D1 signal, which suggests that DEN-induced hepatocellular tumors of mice at the stage of adenoma do not require nuclear β-catenin for the initial stages of Cyclin D1 upregulation. On the other hand, however, the disruption of the Wnt/β-catenin pathway in the present study worked to suppress Cyclin D1 in the mouse tumors, which is similar to what has been frequently reported in studies using mouse models of HCC (4,13,20,22,36,46).…”
Section: Discussionsupporting
confidence: 72%
“…Although the role of Wnt-1, β-catenin and FLZ-1 in the early preneoplastic stages of DEN-induced liver cancer cannot be definitively excluded, our results do not confirm that Wnt-1 blockade counteracts hepatocellular tumors, by contrast to previous studies (20,22,23). It should be noted, however, that those studies base their conclusions on experiments using HCC cell cultures and tumor transplant mouse models grafted with HCC rather than hepatocellular adenoma cells (20,22,23). β-catenin which is an important downstream molecule of Wnt-1-FLZ1 binding is mutated in mice treated with DEN and phenobarbital but not in those treated with DEN alone (4,44).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…At the time of writing, ~1,000 miRNAs have been identified in humans (10). miRNAs are believed to modulate more than a third of human genes (11) and therefore serve notable functions in a large number of biological processes, including cell proliferation, cell cycle, apoptosis, differentiation, metabolism, migration and invasion (12)(13)(14). Furthermore, increasing evidence has demonstrated that the abnormal expression of miRNAs contributes to the initiation and development of human malignancies, including HCC (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%